Effect of prepregnancy maternal BMI on adverse pregnancy and neonatal outcomes: results from a retrospective cohort study of a multiethnic population in Qatar - Shazia Shaukat; Ula Nur (BMJ Open)
Background Given the small number of studies on the topic, we aimed to identify the impact of prepregnancy maternal body mass index (BMI) on adverse pregnancy outcomes (POs) in a low-risk, multiethnic population, and to calculate related population attributable fractions (PAFs).Methods This retrospective cohort study included 1134 nulliparous women of 50 nationalities (classified into Arab and non-Arab ethnicity) in Qatar who had their first antenatal visit at a Primary Healthcare Corporation (PHCC) facility in June 2016–March 2017 and their PO at a Hamad Medical Corporation facility before 10 November 2017. We used multiple imputation to handle missing values and multivariate logistic regression to calculate adjusted ORs (aORs) for adverse POs in overweight and women with obesity.Results Overweight Arab women and women with obesity were at high risk for gestational diabetes mellitus (GDM) (aOR=2.38, 95% CI 1.51 to 3.84) and caesarean section (aOR=1.57, 95% CI 1.00 to 2.48). Non-Arab women with obesity were at high risk for pre-eclampsia (aOR=3.83, 95% CI 1.00 to 15.00). PAFs showed that 41.63% of pre-eclampsia, 17.36% of pregnancy-induced hypertension, 17.17% of large for gestational age, 15.89% of preterm deliveries, 14.75% of GDM and 13.99% of caesarean sections could be avoided if all mothers had normal prepregnancy BMI. There were no major differences in PAFs by ethnicity.Conclusion Adverse POs were attributable to maternal obesity. This suggests that, in contrast to existing PHCC protocol, overweight and women with obesity in Qatar should be targeted earlier in their pregnancy; preferably prior to getting pregnant. We observed ethnic differences in the risk of adverse POs.